THE OPPORTUNITIES OF THE APPLICATION OF ISLAMIC CRIMINAL LAW ACCORDING TO INDONESIAN CONSTITUTION - Heradhyaksa, Bagas; Jamal, Jasri (Journal of Islamic Law Studies, 2021)
Islamic Criminal Law explains criminal offence and the punishments based on Islamic Law. The aim of Islamic criminal law is to maintain peace in the societies, whether for Muslim and non-Mus- lim, and reform the offenders. Running the Islamic criminal law is the right of every Muslim. The Indonesian Constitution guarantees the citizen’s freedom to run their own religion. In this context, running Islamic criminal law is part of Islamic religion. The objective of this paper is to know the opportunities of the application of Islamic criminal law according to Indonesian Constitution. This qualitative study will analyze the library data by referring to the books, the regulation in Indonesia and other sources that support this issue. Thus this paper is expected to generate the information about the possibility of the application of Islamic criminal law in Indonesia according to the Indone- sian Constitution which is the highest law in Indonesia.